PENGGUNAAN STANDARD WBS (WORK BREAKDOWN STRUCTURE) PADA PROYEK BANGUNAN GEDUNG - Ayu Herzanita (Jurnal Infrastruktur, 2019)
WBS (Work Breakdown Structure) plays an important role in every construction project. WBS is a hierarchy of decreasing scope of work to become the smallest level called a work package, making it easier in the process of project management and control. The current problem is that many contractors in Indonesia, both large and small contractors, do not understand the importance of using WBS in a construction project. This causes project performance to be less than optimal, especially on cost and time performance. Currently, WBS standards have been developed for building projects. In this study will look at the cost and time performance of the project from the use of WBS standard building. The sample used in this study are projects that have applied the use of project standards. The projects include Building X, Lecture Building Y, and Sports Facility Building Z. The method used in this study is the EVM (Earn Value Method) approach, collecting data using questionnaires. The results showed that using the WBS standard had an effect on cost and time performance. Good cost and time performance is shown in the Building X and Lecture Y buildings. While the cost and time performance of the Z Sports Facility Building tends to be unstable. This is because the work items that exist in the WBS standard are not in accordance with the project conditions, so it is necessary to adjust work items.